The ethics of tourism development - Smith, Mick, 1961- (Routledge/contemporary geographies of leisure, tourism, and mobility., 2003)
Draws upon a variety of important philosophical traditions to develop an original perspective on the relations between ethical, economic and aesthetic values in a tourism context.